Munasabah Al-Qur’an Dan Relevansinya Dalam Pendidikan - Oqy Andaresta; Nur Kholis (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2022)
As a method of life, the Qur'an is an interconnected whole and explains its components. The whole Qur'an must be considered, not just a part of it. Researchers want to juxtapose the content of the Koran with its relevance in the world of education. The aim is to find out the role of the Qur'an in the world of education. The method used in this research is library research by taking data from existing books and journals. The results of this study indicate that the Koran has relevance to education. Everything in the world of education has been explained in the Qur'an, therefore it is important for us to study the verses of the Qur'an with the letters in the Qur'an. because the verses with each other can be interconnected even between verses in one letter with another letter are interconnected. The relationship between verses and verses, verses and letters is called munasabah al-quran. As in QS. al Najm: 26 which relates to the previous sura related to education.